Effect of Angiotensin-Converting-Enzyme Inhibitor and Angiotensin II Receptor Antagonist Treatment on ACE2 Expression and SARS-CoV-2 Replication in Primary Airway Epithelial Cells - Okoloko, Oghenemega; Vanderwall, Elizabeth R.; Rich, Lucille M.; White, Maria P.; Reeves, Stephen R.; Harrington, Whitney E.; Barrow, Kaitlyn A.; Debley, Jason S. (Frontiers in Pharmacology, 2021)
Rationale: SARS-CoV-2 gains entrance to airway epithelial cells (AECs) through binding of the viral spike protein to the angiotensin-converting enzyme 2 (ACE2) on the cell surface. However, ACE2 also converts angiotensin II into angiotensin-(1-7) and counterbalances the renin-angiotensin-aldosterone system, with resultant protective effects in the cardiovascular system. Some data suggest that two common antihypertension medications (angiotensin II receptor antagonists, ARBs; and angiotensin-converting-enzyme inhibitors, ACEIs) may increase ACE2 expression in heart and kidney cells, fueling debate about how these widely used medications may modulate SARS-CoV-2 infectivity and risk of COVID-19. Aim: Determine whether exposure of bronchial AECs to the ARB losartan or the ACEI captopril modulate expression of ACE2 by AECs, SARS CoV2 replication, or expression of proinflammatory cytokines and type I and III interferon (IFN) responses. Methods: Primary bronchial AECs from children and adults (n=19; ages 8-75 yrs.) were differentiated ex vivo at an air-liquid interface to generate organotypic cultures. Cultures were treated with captopril (1μM) or losartan (2μM) with culture media changes starting 72 hrs. before infection with SARS-CoV-2. In a biosafety level 3 (BSL-3) facility, cultures were infected with SARS-CoV-2 isolate USA-WA1/2020 at a multiplicity of infection (MOI) of 0.5. At 96 hrs. following infection, RNA and protein were isolated. SARS-CoV-2 replication in cultures was assessed with quantitative PCR (qPCR). ACE2, IL-6, IL-1B, IFNB1, and IFNL2 expression were assessed by qPCR. Results: Neither captopril nor losartan treatment significantly changed ACE2, IL-6, IL-1B, IFNB1, or IFNL2 expression by AECs as compared to SARS-CoV-2 infected AEC cultures without captopril or losartan treatment. At 96 hrs. following infection, SARS-CoV-2 copy number/ng RNA was not significantly different between untreated AEC cultures, cultures treated with captopril, or cultures treated with losartan. Conclusion: These findings suggest that at the level of the airway epithelium neither the ACEI captopril or ARB losartan significantly modify expression of the SARS-CoV-2 entry factor ACE2, nor does either medication increase replication SARS-CoV-2 replication. This ex vivo data is reassuring and is consistent with evolving clinical data suggesting ACEIs and ARBs do not increase the risk for poor prognosis with COVID-19 and may actually reduce the risk of COVID-19 disease.